ANALISIS RISIKO KESELAMATAN KERJA PADA PROYEK PENGEMBANGAN BANDARA INTERNASIONAL JUANDA TERMINAL 2 SURABAYA - Reny Indrayani (Fakultas Kesehatan Masyarakat, Universitas Jember, 2017)
The construction sector played an important role in development and was the biggest contributor of work accident rate in Indonesia. The aim of the research were to analyze human, methods, machines, materials, and environment element as cause of occupational accidents. This was a cross-sectional observational research conducted in October 2012 to March 2013. This research was carried out with several integrates stages which include risk identification, risk assessment and priorities formulation, root cause analysis, and ended by recommendations for controlling risk and hazard. Risk identificationshowed that there were 100 risks that couldthreaten the workers. The following categories were: 4% low risk categories, 48% moderate risk, 39% high risk, and 9% extreme risk. Through the Q sort technique obtained five priority safety issues: workers falling from height, electric shock, workers stung by material lifted, fires or explosions, and the scaffolding collapsed. Based on root cause analysis, it showed that the most likely root cause of the problems was dominated by the human factor such as: fatigue due to overtime work, lack of experience and understanding of the procedure, lack of awareness of the importance of the ocupational safety and health. Keywords: construstion,risk assessment, root cause.